2013
DOI: 10.1021/ja311261s
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Face-Centered-Cubic Ruthenium Nanoparticles: Facile Size-Controlled Synthesis Using the Chemical Reduction Method

Abstract: We report the first discovery of pure face-centered-cubic (fcc) Ru nanoparticles. Although the fcc structure does not exist in the bulk Ru phase diagram, fcc Ru was obtained at room temperature because of the nanosize effect. We succeeded in separately synthesizing uniformly sized nanoparticles of both fcc and hcp Ru having diameters of 2-5.5 nm by simple chemical reduction methods with different metal precursors. The prepared fcc and hcp nanoparticles were both supported on γ-Al2O3, and their catalytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
395
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(421 citation statements)
references
References 42 publications
17
395
0
Order By: Relevance
“…For example, it was found that FCC Ru catalysts were more catalytically active for CO oxidation than HCP Ru catalysts. 12 In summary, we identify theoretically that, for CO activation in the presence of hydrogen, HCP Co catalysts have remarkably higher intrinsic activity than FCC Co catalysts, and HCP Co catalysts prefer the direct dissociation route while FCC Co catalysts prefer the H-assisted route. The great influence of crystallographic structure and corresponding morphology effect on formation of the various active sites with higher intrinsic activity and density is illustrated.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 73%
“…For example, it was found that FCC Ru catalysts were more catalytically active for CO oxidation than HCP Ru catalysts. 12 In summary, we identify theoretically that, for CO activation in the presence of hydrogen, HCP Co catalysts have remarkably higher intrinsic activity than FCC Co catalysts, and HCP Co catalysts prefer the direct dissociation route while FCC Co catalysts prefer the H-assisted route. The great influence of crystallographic structure and corresponding morphology effect on formation of the various active sites with higher intrinsic activity and density is illustrated.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 73%
“…An intriguing example are tens of nanometers large Co nanoparticles stabilized in the fcc phase at ambient conditions while bulk Co crystallizes in hexagonal close-packed (hcp) structure [4,7]. Besides cooling, other preparation routes like high-pressure torsion, milling, epitaxial growth, chemical reduction, and microwave irradiation have been proven fruitful to stabilize pure metals in non-equilibrium crystalline phases of their phase diagram (e.g., fcc Fe nanoparticles [8][9][10], fcc Co films [11]) or to reveal unique crystalline phases, i.e., phases not * stesch@kth.se † xiaoqli@kth.se known from their pressure-temperature phase diagram (e.g., nanoparticles of fcc Ru [12], fcc Zr [13], tetragonal Ag [14], fcc Hf [15], and bcc Co films [16]). The common interest that drives current research on such nanostructured materials is related to their potentially shape-or size-enhanced mechanical, magnetic, optical, electronic, or catalytic properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [109] observed the crystal phase evolution of Fe-Pt alloys from fcc to face-centered tetragonal (fct) at high temperature during the synthesis. Afterwards, under controlled synthetic conditions, hexagonal close-packed (hcp, 2H type) and 4H Au, [87,110] body-centered tetragonal (bct) Ag [111], fcc Fe [112], hcp Ni [113], fcc Ru [114] and hcp Rh [99] nanostructures can be prepared. In addition, during some typical growth stages such as seed growth, ligand exchange, and metal coating, the unusual phase or phase evolution can be also observed.…”
Section: Phase Evolutionmentioning
confidence: 99%